Towards the Development of Mobile App Design Model for Dyscalculia Children in Malaysia - Abd Halim, F.A. (EDP Sciences, 2018)
Learning disabilities (LD) are problem that influence the brain capacity to receive, process, analyse and store information. These processing issues can interfere with learning fundamental abilities, for example, reading (Dyslexia), writing (Dysgraphia) and math (Dyscalculia). Fortunately, in today's world technology, we have numerous option techniques for educating and supporting fundamental skills in reading, writing and math such as mobile learning by using mobile app. However, the research in mobile app design model for Dyscalculia children is still scarce: very few studies have focus on how to design and develop appropriate mobile app for Dyscalculia children from the perspective of mobile app designers and developers. The purpose of this paper is to identify the appropriate components that should be included in the mobile app model. Interview sessions were conducted with Dyscalculia practitioners that involved a teacher, paediatric and an educational psychology. This has resulted in identifying 16 components that can be included in the mobile app design model. Â© The Authors, published by EDP Sciences, 2018.